2017
DOI: 10.1002/2016jc012439
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of El Niño events on the Peruvian upwelling system productivity

Abstract: Every 2–7 years, El Niño events trigger a strong decrease in phytoplankton productivity off Peru, which profoundly alters the environmental landscape and trophic chain of the marine ecosystem. Here we use a regional coupled physical‐biogeochemical model to study the dynamical processes involved in the productivity changes during El Nino, with a focus on the strongest events of the 1958–2008 period. Model evaluation using satellite and in situ observations shows that the model reproduces the surface and subsurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 90 publications
7
71
0
Order By: Relevance
“…Garreaud, 2018). Montes et al, 2011;Espinoza-Morriberón et al, 2017). However, Zamora et al (2012) reported uniform oxygen concentrations for waters in the 395 PCUC; therefore there is no oxygen change due to changes in alongshore advection, explaining the weak oxygen change in our study.…”
Section: Summary and Discussion 345mentioning
confidence: 52%
“…Garreaud, 2018). Montes et al, 2011;Espinoza-Morriberón et al, 2017). However, Zamora et al (2012) reported uniform oxygen concentrations for waters in the 395 PCUC; therefore there is no oxygen change due to changes in alongshore advection, explaining the weak oxygen change in our study.…”
Section: Summary and Discussion 345mentioning
confidence: 52%
“…Models with unrealistically tilted OMZ are too sensitive to changes in zonal flow and show strong interannual variations in the depth of their upper boundary. In this study, we showed the importance of the EUC mean state and temporal variability for the OMZ, but the existence of systematic biases in the circulation is also relevant in the context of heat (Coats & Karnauskas, 2018) and nutrients (Qin Xuerong et al, 2016) transport to the equatorial Pacific and "downstream" regions like the Peruvian coast (Montes et al, 2010;Espinoza-Morriberón et al, 2017). The relationship found between OMZ tilt and OMZ sensitivity to EUC changes is therefore likely to be relevant in the context of forced climatic changes.…”
Section: Discussionmentioning
confidence: 54%
“…Improving the representation of the EUC appears a necessary step to improve projections of the OMZ and possibly reconcile models disparate future trends. In this study, we showed the importance of the EUC mean state and temporal variability for the OMZ, but the existence of systematic biases in the circulation is also relevant in the context of heat (Coats & Karnauskas, 2018) and nutrients (Qin Xuerong et al, 2016) transport to the equatorial Pacific and "downstream" regions like the Peruvian coast (Montes et al, 2010;Espinoza-Morriberón et al, 2017). Code and data to reproduce the results of this study are provided in Zenodo archives (https://zenodo.org/record/ 3236505, https://zenodo.org/record/ 2648855).…”
Section: Geophysical Research Lettersmentioning
confidence: 66%
“…N1 + 2 comprises the area between 80 -90 W, 0 N-10 S in the Tropical Pacific Ocean, based on a 2 grid data of the Extended Reconstruction of Historical Sea Surface Temperature version 3b (ERSSTv3b; Smith et al, 2008) and was obtained from NOAA CPC (Climate Prediction Center) (NOAA, 2015) for the same period. Thermocline depth off Peru (called here Z15) is the depth of the 15 C isotherm obtained from IMARPE, details about its calculations can be found in Espinoza-Morriberón et al (2017). The period covered was 1982-2008.…”
Section: Datamentioning
confidence: 99%